A Silent Public Health Crisis: Untreated Caries and Dental Infections Among 6- and 12-Year-Old Children in the Philippine National Oral Health Survey 2006. (March 2015) - Monse, Bella; Benzian, Habib; Araojo, Juan; Holmgren, Christopher; van Palenstein Helderman, Wim; Naliponguit, Ella-Cecilia; Heinrich-Weltzien, Roswitha
The oral health status of 6- and 12-year-old Filipino children was assessed in a representative national sample of 2030 6-year-old and 2022 12-year-old children, using WHO Basic Methods for Oral Health Surveys (4th edition, 1997) and the PUFA (pulpal involvement [P/p], ulceration caused by dislocated tooth fragments [U/u], fistula [F/f], and abscess [A/a]) index. A subsample of 242 12-year-old children was included to assess backward comparability between the 1998 Oral Health Survey that used WHO Basic Methods (3rd edition, 1987). The results showed that 97% of 6-year-old children had caries (mean dmft 8.4), 85% showed dental infection (mean pufa 3.4), 20% reported pain when examined. In all, 82% of 12-year-old children had caries (mean DMFT 2.9), 56% prevalence of pulp involvement (mean PUFA 1.0), and 16% reported pain when examined. Differences in methodology between the 1998 and the 2006 surveys are likely to have had an effect on the observed reduction in DMFT, indicating that the real caries prevalence had not changed much and remains very high.